1996
DOI: 10.1016/0014-5793(96)01103-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of ETB receptors in local clearance of endothelin‐1 in rat heart: studies with the antagonists PD 155080 and BQ‐788

Abstract: The effects of two endothelin (ET) receptor antagonists, PD 155080 (ETA selective) and BQ-788 (ETB selective), on cardiac function and ET-1 release were studied in isolated rat hearts. In normoxic hearts, infusion of PD 155080 (50 nM-5 oM) reduced coronary resistance, but had no effect on ET-1 release. Low concentrations of BQ-788 (2 and 20 nM) had no effect on coronary resistance; high concentrations (0.2 and 2 gM) increased it ,-.2-fold; all concentrations increased ET-1 release (up to 24-fold). Similar resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 26 publications
2
22
0
3
Order By: Relevance
“…Several studies have suggested that ET B receptors may act as clearance receptors for ET-1, 22 and the observation that ET-1 binding to ET B receptors is less stable than its binding to ET A receptors 19 supports the above hypothesis. Because the total density of ET B receptors is higher in ventricular membranes than in myocytes, it may be speculated that ET B receptors may contribute to preventing excessive ET-1 myocardial concentrations.…”
Section: Myocyte Et-1 Subtype Receptorssupporting
confidence: 62%
“…Several studies have suggested that ET B receptors may act as clearance receptors for ET-1, 22 and the observation that ET-1 binding to ET B receptors is less stable than its binding to ET A receptors 19 supports the above hypothesis. Because the total density of ET B receptors is higher in ventricular membranes than in myocytes, it may be speculated that ET B receptors may contribute to preventing excessive ET-1 myocardial concentrations.…”
Section: Myocyte Et-1 Subtype Receptorssupporting
confidence: 62%
“…Additionally, ET B receptors have been suggested to play a role as endothelin clearance receptors. 33 Blockade of ET B receptors may, therefore, influence vascular reactivity and arterial pressure by increasing endogenous endothelin levels and activating ET A receptors. This proposition is supported by reports that the increased susceptibility to deoxycorticosterone acetate (DOCA) -salt-induced hypertension and vascular and renal injuries in ET B receptor-deficient rats was reduced during chronic treatment with an ET A receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Brunner and Doherty 42 have demonstrated that BQ-788, an ET B receptor antagonist, increases ET-1 release and elevates coronary resistance in isolated rat hearts. They suggested that cardiac ET B receptors were involved in the local sequestration and clearance of ET-1, both in ischemic and nonischemic situations, and that ET-1 displaced by the ET B antagonist stimulated ET A receptors, which resulted in coronary constriction.…”
Section: Discussionmentioning
confidence: 99%